The Influence of Motivation and Quality of Work Life on Intention to Stay with Job Satisfaction as an Intervening Variable among Employees at Perumda Air Minum Kota Sangatta - Rahayu, Ayu; Triatmanto, Boge; Setiyadi, Sina (Yayasan Inovasi Akademi Nusantara, 2025)
This study aims to explore, examine, and analyze the influence of motivation and quality of work life on the intention to stay, with job satisfaction serving as a mediating variable. The research employs a quantitative approach, utilizing data analysis techniques through SmartPLS software based on Structural Equation Modeling (SEM-PLS). The study population consists of all employees at Perumda Air Minum Kota Sangatta, characterized by heterogeneity. The sample size was determined using the Slovin formula, resulting in a total of 109 respondents. The findings reveal that motivation has a positive and significant effect on job satisfaction, as does quality of work life. Furthermore, motivation directly and significantly influences the intention to stay, while quality of work life does not have a significant effect on that variable. Subsequent results indicate that job satisfaction positively and significantly affects the intention to stay and acts as a mediating variable in the relationship between motivation and intention to stay, as well as between quality of work life and intention to stay. These findings highlight the critical role of job satisfaction as a key factor in employee retention.